The benefit of whole brain reirradiation in patients with multiple brain metastases - (:unkn) unknown (BIOMED CENTRAL LTD, 2013)
Background: To assess the outcomes, symptom palliation and survival rates in patients who received repeat whole brain radiotherapy (WBRT). Methods: Twenty-eight patients who had progression of brain metastasis received a second course of WBRT. Univariate log-rank testing and multivariate Cox regression analysis were used to determine the factors for death among several variables (cumulative BED [BEDcumulative], primary tumor site, Karnofsky performance scale [KPS], previous SRS, number of metastases and absence of extracranial metastases). Correlations between variables and treatment response were evaluated with the Chi-squared test. Results: The median KPS was 60 (range 50 to 100) at the initiation of reirradiation. The median time interval between the two courses of WBRT was 9.5 months (range 3-27 months). The median doses of the first course and the second course of WBRT were 30 Gy (range 20 to 30 Gy) and 25 Gy (range 20 to 30 Gy), respectively. The mean BEDcumulative was 129.5 Gy (range 110 to 150 Gy). Severe or unexpected toxicity was not observed. Symptomatic response was detected in 39% of the patients. The median overall survival following reirradiation was 3 months (range 1 to 12 months, 95% CI 1.82-4.118). Survival was significantly better in responders (median 10 months, 95% CI 3.56-16.43) compared with non-responders (median 2 months, 95% CI 1.3-2.64) (p = 0.000). In multivariate analysis, patients that had lung cancer (p = 0.01), initial KPS >= 60 (p = 0.03) or longer intervals to reirradiation (p = 0.01) had significantly better survival rates. Conclusions: A careful second course of whole brain irradiation might provide a symptomatic and survival benefit in patients with good performance status and longer cranial progression-free intervals.
Keywords: Brain metastases; Cancer; Reirradiation; Whole brain radiotherapy; IRRADIATION